1987
DOI: 10.1111/j.1439-0442.1987.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maturational Changes Upon the Orientation of Auricular Activation Vector in Sheep

Abstract: The consequences of physical maturation on the orientation of the mean vector of auricular activation in Merino Precoz sheep at different ages has Peen analysed.The results show that the vectorial magnitudes of AP and SAP undergo a significant decrease at 20 days and between 3 months and 1 year of age. Conversely, physical maturation does not seem to have any effect on the sequence of auricular activation, since the P mean spatial vector takes a sinistrocaudal and slightly ventral orientation in all ages analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…As the lambs grew, the amplitude of the P wave declined, with values declining until they became similar to those described for adults. Adults have the lowest P wave range because of their larger body size, which increases the distance between the electrode and the focus of atrial depolarization, promoting a lower voltage [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the lambs grew, the amplitude of the P wave declined, with values declining until they became similar to those described for adults. Adults have the lowest P wave range because of their larger body size, which increases the distance between the electrode and the focus of atrial depolarization, promoting a lower voltage [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previously applied in other species, it is probably less valuable to justify the selection of a lead system on the basis of the variability of results issued from a large number of subjects. Indeed, the between-calf variability obtained in this study could be attributed not only to the technique, but also to confounding variables such as age (VAN ARSDEL et al, 1963;GHERGARIU et al, 1970;HAMLIN et al, 1972;LIEBMAN and PLONSEY, 1977;LOMBARD et al, 1984;SANTISTEBAN eta]., 1986;SANTISTEBAN et al, 1987b;TOVAR and SANTISTEBAN, 1987a;TOVAR and SANTISTEBAN, 1987b;RUBIO et al, 1989a;RUBIO et al, 1989b), breed (SMITH et al, 1957; VAN ARSDEL et al, 1963;PIPBERGER et al, 1967;WALKER and WALKER, 1969;SCHULTZ and PRETORIUS, 1972;UNSHELM et al, 1974;MORGANROTH and MARON, 1977;FREGIN, 1982), bodily conformation (HAMLIN and SMITH, 1960;IKAHEIMO et al, 1979;DITCHEY et al, 1981) or sex (WALKER and WALKER, 1969) of the subjects. However, when the Ei, Ha and Mu lead system were used, the P, QRS and T modal horizontal vectors magnitude and angles showed very large differences between the calves (Tables 4 and 5, Fig.…”
Section: Discussionmentioning
confidence: 73%
“…So large between-subject variations may not be interpreted as physiological. Several authors (BROOIJMANS, 1957;SMITH et al, 1957; VAN ARSDEL et al, 1959;HOLMES and DARKE, 1970;HOLMES and ELSE, 1972;Buss et al, 1975;SZABUNIEWICZ and CLARK, 1976;UPADHYAY et al, 1976;DE ROTH, 1980;FREGIN, 1982;SANTISTEBAN et al, 1987a;RUBIO et al, 1989 a) also reported, in large animals, wide variations in electrocardiographic data measured in the horizontal plane when classical limb leads, or leads derived therefrom, are used. This may be due to the fact that the limb leads are unable to produce vectocardiographic data representative of the true cardiac electric field .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECG studies in sheep and dogs have shown age-related variations (2,24). But there were no major differences between sexes for ECG parameters of the dogs have been reported (8).…”
Section: Discussionmentioning
confidence: 97%